Adopting a risk-based approach for non-profit organisations - Murrar, Firas (Journal of money laundering control, 2022)
Purpose This study aims to define how countries can implement a risk-based approach (RBA) for non-profit organisations (NPOs) by measuring how well certain countries have complied with the Financial Action Task Force’s (FATF) “Recommendation 8, criterion 1” (recommendation [8.1]). Design/methodology/approach This study combines a comparative analysis methodology with a descriptive analytical approach to compare three member countries of FATF and FATF-Style Regional Bodies (FSRBs). It uses secondary data sources, namely, FATF guidelines on the subject and FATF reports on mutual evaluation reports. Findings This study examines the variations in compliance with the FATF recommendation (8.1) among three countries recently assessed by the FATF: the UK, Bahrain and the Russian Federation. Although the UK has completely fulfilled these recommendations, Bahrain and Russia have largely fulfilled them. These variations in compliance are mainly attributed to the uneven level of preparedness in the countries’ commitment to the legislative requirements before the process of mutual evaluation. Originality/value This paper offers insight into the progress of legislation and mechanisms (technical compliance) in the three countries with respect to recommendation (8.1). This paper also discusses the evolution of implementing and adopting the RBA among NPOs. This paper concludes with suggestions to other countries in developing a plan that meets the FATF recommendations by considering key factors such as comprehensive assessment of threats to NPOs, periodic reassessment and sharing of success stories.